1996
DOI: 10.1002/(sici)1097-0142(19961001)78:7<1477::aid-cncr15>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol and omeprazole in the prevention of chemotherapy-induced acute gastroduodenal mucosal injury: A randomized, placebo-controlled pilot study

Abstract: The strong and prolonged inhibition of gastric acid production induced by omeprazole seems to be effective in preventing chemotherapy-induced gastroduodenal mucosal injury. Further trials are necessary to verify whether such a prevention of endoscopically observed injury can translate into prevention of clinically significant injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Two sequential randomized trials assessed the use of PPIs as prophylactic agents during chemotherapy. The first trial randomized patients undergoing chemotherapy with the CMF regimen (Cyclophosphamide, Methotrexate, and Fluorouracil) for breast cancer and a combination of Fluorouracil and Leucovorin for colorectal cancer (Sartori et al, 1996). Patients underwent an endoscopy before randomization and a further one 7 days after the second cycle.…”
Section: Chemotherapy-induced Gastric Damagementioning
confidence: 99%
See 1 more Smart Citation
“…Two sequential randomized trials assessed the use of PPIs as prophylactic agents during chemotherapy. The first trial randomized patients undergoing chemotherapy with the CMF regimen (Cyclophosphamide, Methotrexate, and Fluorouracil) for breast cancer and a combination of Fluorouracil and Leucovorin for colorectal cancer (Sartori et al, 1996). Patients underwent an endoscopy before randomization and a further one 7 days after the second cycle.…”
Section: Chemotherapy-induced Gastric Damagementioning
confidence: 99%
“…Endoscopically-documented mucosal damage was evident in nearly half of the patients after the second cycle in the non-Omeprazole arms. Some limitations of the two chemotherapy trials (Sartori et al, 1996(Sartori et al, , 2000, together with additional concerns, should be taken into account. First of all, gastric damage did not translate into clinically relevant consequences, such as bleeding, anemia, or perforation.…”
Section: Chemotherapy-induced Gastric Damagementioning
confidence: 99%
“…Good efficacy of ranitidine during various combination chemotherapies has been reported. 4 Our findings suggest that omeprazole may block renal elimination of MTX. One other case 11 of this interaction has been reported; however, in our patient, MTX elimination did not return to normal values as quickly as described in that case.…”
Section: Case Reportsmentioning
confidence: 99%
“…Furthermore, it has been reported that a decrease in gastric mucosal blood fl ow (GMBF) is involved in the pathogenic mechanism of gastric lesions in response to chemotherapy (Kakinuma et al, 1997). In addition, these symptoms induced by anti-cancer drugs were reportedly ameliorated by the treatment with histamine H 2 receptor antagonists or proton pump inhibitors (Sartori et al, 1996(Sartori et al, & 2000.…”
Section: Introductionmentioning
confidence: 99%